Loneliness and the risk of dementia among older Chinese adults: gender differences. (3rd April 2018) - Zhou, Zi; Wang, Ping; Fang, Ya
ABSTRACT: Objective: The objective of this study was to examine whether loneliness was associated with the risk of developing dementia in Chinese older adults and whether the association was moderated by gender. Method: A 3-year cohort study was conducted using data from the 2008/2009 and 2011/2012 waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Multiple logistic regression was used to analyze the relationship between loneliness and dementia. The interaction between loneliness and gender was also evaluated. Results: At 3-year follow-up, 393 of the 7867 participants had dementia. Loneliness was associated with dementia (odds ratio (OR) = 1.31, 95% confidence interval (CI) = 1.11–1.56) after adjustment for sociodemographic characteristics, lifestyle, and baseline health status. A significant interaction between loneliness and gender was also found (OR = 0.81, 95% CI = 0.65–0.99). Conclusion: Loneliness increased the risk of developing dementia among people aged 65 years and older in China. Moreover, the effect of loneliness on dementia risk varied by gender. Specifically, men who felt lonely were more likely to suffer from dementia than women.